(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The objective of the present study was to evaluate the effects of using dried chaya leaf meal (DCLM) as a protein feed in a diet on growth performance, blood profiles, and carcass quality in a native Thai chicken. Materials and Methods: Eighty 14-day-old Pradu Hangdum chicks were divided into four groups with four replicates each: control (without DCLM), 10%, 20%, and 30% DCLM inclusion in mash feed. Growth performance was recorded weekly until 98 days of age. Blood profile, carcass quality, and visceral organ weight were measured at 98 days of age. Results: The 10%–30% DCLM inclusion in the diet did not affect feed intake or feed efficiency; however, the body weight gain of chicks decreased linearly with the increase in DCLM inclusion. The heterophils, eosinophils, and monocytes were linearly increased with the increasing DCLM levels in the groups. The serum blood chemistry did not differ among the groups, while the AST in 10% and 20% DCLM was lower than in the control. Increasing the level of DCLM in the chicken diet did not affect carcass quality. Conclusion: The DCLM can be used as a feed ingredient in Thai native chicken feed up to 20%. J. Adv. Vet. Anim. Res., 10(1): 51–56, March 2023 http://doi.org/10.5455/javar.2023.j651